PENDEKATAN SUSTAINABLE LIVELIHOOD FRAMEWORK DALAM PERENCANAAN PEMBANGUNAN DESA - Vediyansyah; Zainal Amaluddin; Azmi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This study aims to determine the extent of the community's role in Village Development Planning through the Sustainable Livelihood Framework approach to achieve sustainable development. Village development planning through the Sustainable Livelihood Framework Approach in Village Development Planning Perspective Village Regulation No. 21 of 2020 Concerning General Guidelines for the Development and Empowerment of Village Communities. This type of research is qualitative research, with an empirical legal research approach, this type of qualitative research is field research. Data collection techniques used are interviews, documentation and observation. The results of the research show that village planning has been carried out through the flow and stages as contained in the existing regulations, however, it needs improvement after changes have been made. In accordance with the mandate of Permendesa No 21 of 2021 concerning General Guidelines for Village Development and Empowerment, Village development planning is carried out by referring to the macros that are owned by the Village in achieving 8 Village typologies and 18 Village SDGs goals, namely sustainable development goals. Conducting a review of village conditions in mapping village problems, potential and assets is the main thing that villages can do using the Sustainable livelihood Framework approach. In an effort to form a sustainable village concept, sustainable livelihoods and can become an independent village, a village that has strong food security in the life of the village community.